Carfilzomib induces leukaemia cell apoptosis via inhibiting ELK1/KIAA1524 (Elk‐1/CIP2A) and activating PP2A not related to proteasome inhibition. (24th March 2017) - Liu, Chun‐Yu; Hsieh, Feng‐Shu; Chu, Pei‐Yi; Tsai, Wen‐Chun; Huang, Chun‐Teng; Yu, Yuan‐Bin; Huang, Tzu‐Ting; Ko, Po‐Shen; Hung, Man‐Hsin; Wang, Wan‐Lun; Shiau, Chung‐Wai; Chen, Kuen‐Feng
Summary: Enhancing the tumour suppressive activity of protein phosphatase 2A (PP2A) has been suggested to be an anti‐leukaemic strategy. KIAA1524 (also termed CIP2A), an oncoprotein inhibiting PP2A, is associated with disease progression in chronic myeloid leukaemia and may be prognostic in cytogenetically normal acute myeloid leukaemia. Here we demonstrated that the selective proteasome inhibitor, carfilzomib, induced apoptosis in sensitive primary leukaemia cells and in sensitive leukaemia cell lines, associated with KIAA1524 protein downregulation, increased PP2A activity and decreased p‐Akt, but not with the proteasome inhibition effect of carfilzomib. Ectopic expression of KIAA1524, or pretreatment with the PP2A inhibitor, okadaic acid, suppressed carfilzomib‐induced apoptosis and KIAA1524 downregulation in sensitive cells, whereas co‐treatment with the PP2A agonist, forskolin, enhanced carfilzomib‐induced apoptosis in resistant cells. Mechanistically, carfilzomib affected KIAA1524 transcription through disturbing ELK1 (Elk‐1) binding to the KIAA1524 promoter. Moreover, the drug sensitivity and mechanism of carfilzomib in xenograft mouse models correlated well with the effects of carfilzomib on KIAA1524 and p‐Akt expression, as well as PP2A activity. Our data disclosed a novel drug mechanism of carfilzomib in leukaemia cells and suggests the potential therapeutic implication of KIAA1524 in leukaemia treatment.